CAROLI’S DISEASE: A DISEASE THAT RARELY COMES TO MIND: A CASE REPORT - Rančić, Andrija (Acta medicae Medianae, 2023)
Caroli’s disease is a rare disease characterized by dilatation of large intrahepatic bile ducts. It occurs in the classic form presented by repeated episodes of cholangitis (Caroli’s disease), as well as in the form of syndrome with the development of fibrosis and cirrhosis of the liver (Caroli’s syndrome). The disease can occur throughout entire life, but mostly before the age of 30. The incidence of this disease is estimated at about 1 in 1,000,000 cases for Caroli’s disease and 1 in 100,000 for Caroli’s syndrome. The main symptoms are: fever, jaundice, itchy skin, pain under the right costal arch, nausea and vomiting. Possible complications are the development of liver fibrosis and cirrhosis and cholangiocellular carcinoma. Diagnosis is made by clinical and ultrasound examination, computed tomography, more often by magnetic resonance cholangiopancreatography and liver biopsy. We present a clinical case of an elderly patient who has been suffering from Caroli’s disease for a few years now. Diagnostic challenges and applied therapy are presented.